A novel sedimentologically controlled accumulation pattern for marine shale gas: insights from the “source-reservoir-seal” configurations of lower Carboniferous shale in the Yaziluo rift trough, Southern China - Chen, Xianglin; Shi, Dishi; Chen, Rong; Li, Fei; Yang, Xiaoguang; Cen, Wenpan; Wang, Yuluo; Xu, Xiaofeng (Frontiers in Earth Science, 2026)
Substantial shale gas discoveries in the rift troughs of southern China have demonstrated significant resource potential in marine shale formations. However, the complex vertical lithofacies architecture, resulting from diverse sedimentary environments and characterized by recurrent alternation of mudstone and argillaceous limestone layers, presents challenges in understanding shale associations characteristics across different sedimentary facies and their associated gas accumulation mechanisms. This study focuses on the Lower Carboniferous shale within the Yaziluo Rift Trough, employing an integrated analytical approach incorporating geochemical characterization, X-ray diffraction, field emission scanning electron microscopy (FE-SEM), and high-pressure methane isothermal adsorption experiments to evaluate various shale associations. Key findings reveal that lower slope facies shale association constitute optimal exploration targets, developing an integrated “source-reservoir-seal” configuration that enhances gas accumulation and retention. Its high-quality reservoirs emerge at lithological transitions zones where interconnected inorganic pore networks and microfracture systems facilitate efficient gas migration from source rocks, resulting in elevated gas accumulation. The upper slope facies shale association exhibit spatially heterogeneous configurations dominated by multiple sets of argillaceous limestone interbeds, forming vertically compartmentalized systems conducive to free gas migration and multi-point accumulation. In contrast, basin facies shale association demonstrate constrained gas retention capacity due to clay-dominated mineralogy and absence of argillaceous limestone interlayers. This study emphasizes the critical role of lithofacies heterogeneity and integrated “source-reservoir-seal” configurations in evaluation of shale gas accumulation, which provides a new paradigm for the exploration of rift trough shale gas.